Microbial Carbonic Anhydrases in Biomimetic Carbon Sequestration for Mitigating Global Warming: Prospects and Perspectives - Bose, Himadri; Satyanarayana, Tulasi (Frontiers in Microbiology, 2017)
All the leading cities in the world are slowly becoming inhospitable for human life with global warming playing havoc with the living conditions. Biomineralization of carbon dioxide using carbonic anhydrase (CA) is one of the most economical methods for mitigating global warming. The burning of fossil fuels results in the emission of large quantities of flue gas. The temperature of flue gas is quite high. Alkaline conditions are necessary for CaCO3 precipitation in the mineralization process. In order to use CAs for biomimetic carbon sequestration, thermo-alkali-stable CAs are, therefore, essential. CAs must be stable in the presence of various flue gas contaminants too. The extreme environments on earth harbor a variety of polyextremophilic microbes that are rich sources of thermo-alkali-stable CAs. CAs are the fastest among the known enzymes, which are of six basic types with no apparent sequence homology, thus represent an elegant example of convergent evolution. The current review focuses on the utility of thermo-alkali-stable CAs in biomineralization based strategies. A variety of roles that CAs play in various living organisms, the use of CA inhibitors as drug targets and strategies for overproduction of CAs to meet the demand are also briefly discussed.